Photovoltaic self-consumption in buildings: A review. (15th March 2015) - Luthander, Rasmus; Widén, Joakim; Nilsson, Daniel; Palm, Jenny
Highlights: Review of papers examining options for increasing residential PV self-consumption. Two main options: battery energy storage and demand side management (DSM). Higher potential for increased self-consumption with battery storage than DSM. Further research needed for a comprehensive view of technologies and potential. Abstract: The interest in self-consumption of PV electricity from grid-connected residential systems is increasing among PV system owners and in the scientific community. Self-consumption can be defined as the share of the total PV production directly consumed by the PV system owner. With decreased subsidies for PV electricity in several countries, increased self-consumption could raise the profit of PV systems and lower the stress on the electricity distribution grid. This review paper summarizes existing research on PV self-consumption and options to improve it. Two options for increased self-consumption are included, namely energy storage and load management, also called demand side management (DSM). Most of the papers examine PV-battery systems, sometimes combined with DSM. The results show that it is possible to increase the relative self-consumption by 13–24% points with a battery storage capacity of 0.5–1 kW h per installed kW PV power and between 2% and 15% points with DSM, both compared to the original rate of self-consumption. The total number of papers is however rather limited and further research and more comparative studies are needed to give a comprehensive view of the technologies and their potential. Behavioral responses to PV self-consumption and the impact on the distribution grid also need to be further studied.